Inorganic nanoparticles to overcome efficiency inhibitors of organic photovoltaics: An in-depth review. (September 2022) - Kamel, Michael S.A.; Al-jumaili, Ahmed; Oelgemöller, Michael; Jacob, Mohan V.
Abstract: Organic photovoltaics (OPVs) have received considerable attention over the past two decades as a promising alternative to their inorganic counterparts. Although the power conversion efficiency (PCE) of OPVs has rapidly increased in the last ten years exceeding 18%, higher PCEs are still needed to commercialize this emerging technology. The weak light absorption, particularly at wavelengths outside the visible region, and the recombination losses of the photo-generated charge carriers represent the major challenges for the PCE of OPVS. The light harvest and survival of the photo-generated charge carriers within OPVs are restricted to multiple factors such as material properties and device engineering. The application of different types of inorganic nanoparticles (INPs) in OPVs has been reported by many researchers as an effective strategy to overcome most of the PCE-limitations. Here, a comprehensive overview of the progress in the performance of OPVs due to the application of different INPs over the past decade is provided. This review also presents an in-depth analysis of the efficiency loss pathways at the different steps of the photovoltaic effect and how INPs can address these issues resulting in PCE enhancement of OPVs. Finally, the impacts of this approach on the stability and cost of the device in addition to challenges and outlook are discussed. Graphical abstract: Image 1 Highlights: A comprehensive overview of the progress in the performance of OPVs made by by different INPs, in the last decade, is presented. An in-depth analysis to the efficiency loss pathways in OPVs, and how INPs can overcome these limitations is provided. The impact of using INPs on the stability and cost of OPVs is discussed An outlook for future research to develop high efficiency OPVs is introduced.